2017
DOI: 10.1007/978-3-319-55330-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Structural and Functional Cardiac Remodeling

Abstract: The heart must function continuously as it is responsible for both supplying oxygen and nutrients throughout the entire body, as well as for the transport of waste products to excretory organs. When facing either a physiological or pathological increase in cardiac demand, the heart undergoes structural and functional remodeling as a means of adapting to increased workload. These adaptive responses can include changes in gene expression, protein composition, and structure of sub-cellular organelles involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 141 publications
1
45
0
4
Order By: Relevance
“…It is worth mentioning that deacetylation of OPA1-but not of other mitochondrial proteins including SOD2-maintained in the long term in Sirt3 -/animals, corrected cardiac dysfunction and fibrosis, demonstrating this maneuvre's previously unanticipated potential for cardiac protection. Studies have shown that mitochondrial dysfunction in cardiomyocytes critically contributes to the development of age-associated cardiac fibrosis by impairing bioenergetics and reducing cell survival (1,28,49). Furthermore, based on the recent evidence that Complex I inhibition is sufficient to promote the development of fibrosis in the lung, it is tempting to infer that the normalization of Complex I activity through mutOpa1 gene transfer contributes to the amelioration of cardiac fibrosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that deacetylation of OPA1-but not of other mitochondrial proteins including SOD2-maintained in the long term in Sirt3 -/animals, corrected cardiac dysfunction and fibrosis, demonstrating this maneuvre's previously unanticipated potential for cardiac protection. Studies have shown that mitochondrial dysfunction in cardiomyocytes critically contributes to the development of age-associated cardiac fibrosis by impairing bioenergetics and reducing cell survival (1,28,49). Furthermore, based on the recent evidence that Complex I inhibition is sufficient to promote the development of fibrosis in the lung, it is tempting to infer that the normalization of Complex I activity through mutOpa1 gene transfer contributes to the amelioration of cardiac fibrosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria play a strategic role in ensuring an adequate EC coupling (Miragoli and Cabassi 2017; Umanskaya et al 2014; Gambardella et al 2017; Torrealba et al 2017). Indeed, cardiac myocytes are critically dependent on constant and appropriate energy supply, alongside with a finely tuned Ca 2+ handling (Torrealba et al 2017; Sorriento et al 2017; Sheeran and Pepe 2017).…”
Section: Role Of Mitochondrial Ca2+ In Metabolism-contraction Coupmentioning
confidence: 99%
“…Indeed, cardiac myocytes are critically dependent on constant and appropriate energy supply, alongside with a finely tuned Ca 2+ handling (Torrealba et al 2017; Sorriento et al 2017; Sheeran and Pepe 2017). Mitochondria and SR are functionally and structurally associated and, at the point of interaction (mitochondrial associated membranes) Ca 2+ transits from SR to mitochondria (Min et al 2012; Bononi et al 2017).…”
Section: Role Of Mitochondrial Ca2+ In Metabolism-contraction Coupmentioning
confidence: 99%
“…ATP also has antiarrhythmic, hypotensive, and anticonvulsant effects (Torrealba et al, 2017). It is also known that ATP stimulates the formation of cyclic AMP, which is a potent vasodilator that influences coronary arteries, in particular, whereas the reduced post-load in combination with improved myocardial circulation is accompanied by increased cardiac performance efficiency (Smolina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, today the interest in studying the ATP action in the body on the whole and under physical loads, in particular, is related to the fact that, during hypoxia, previously unknown properties of this substance as an endogenous intracellular regulator of cell functions and intercellular messenger tend to be manifested. It has been recently shown that protective effect of ATP on the body is mediated by both the restoration of macroergic substrate pool and the impact on the pathways of the receptor signal transmission, accompanied by changes in the expression of some genes (Liu et al, 2017;Torrealba et al, 2017), and increased activity of several enzymatic complexes, which determines cell metabolism on the whole. Within internal environment of a cell, the ATP molecule is in charge of the energy, including going through localized intracellular receptors to ATP, where it blocks the sensitive potassium channels, breaking down adenosine, moving outside, and influencing potassium channels (Smolina et al, 2017) through their activation.…”
Section: Introductionmentioning
confidence: 99%